Caesarean sections and outcomes of labor induction after the introduction of a new intravaginal device: retrospective analysis - Veronika Anzeljc; Faris Mujezinović (Clinical and Experimental Obstetrics & Gynecology)
Background: To evaluate the outcomes and process of labour induction following the introduction of a new vaginal device with slow releasing dinoprostone (Propess). Methods: Data were collected on the indications for labour induction, the process of induction and delivery, and the outcomes of delivery for 171 term pregnancies between 1 January 2020 and 31 August 2020. Excluded from this study were patients with preterm delivery, multiple pregnancies, or pre-labour rupture of membranes. Data for the standard dinoprostone medication (PG) and Propess groups was analysed and compared. Results: Of the 93 women (54.4% of total) induced in the PG group, 55 (59.1%) received Prostin tablets, 17 (18.3%) received 1 mg of Prostin gel, and 21 (22.6%) received 2 mg of Prostin gel. Seventy eight women (45.6%) received the new intravaginal device (Propess group). The five most frequent indications for labour induction were post-term pregnancy (53, 31.0%), GDM (42, 24.6%), oligohydramnios (30, 17.5%), IUGR (21, 12.3%), and hypertensive disease (20, 11.7%). The Bishop scores were unfavourable in the majority of cases (119, 69.6%). The length of induction was less than 24 hours in 134 women (78.4%). Oxytocin was used more frequently (p = 0.001) in the Propess group and these women underwent more frequent caesarean section (20.5% vs 12.9%, p = 0.31). The status of babies was good in both groups. Conclusion: Introduction of the Propess device to mainstream medical practice has led to rapid implementation and resulted in improved workflow and positive outcomes for both the baby and mother.